The Contribution of the Fatimid Dynasty to the Development of Knowledge in Islamic Civilization: A Historical Study - Iqbal; Firdaus (Sao Literasi Publisher, Yayasan Pendidikan Khaerul Munif, 2026)
The Fatimid Dynasty (909–1171 CE) was one of the Islamic dynasties that made significant contributions to the advancement of knowledge through the strengthening of the educational system, the establishment of scholarly institutions, and sustained support for the intellectual activities of scholars and scientists. However, these contributions have often been overshadowed by the predominance of studies on the Abbasid Dynasty, thereby necessitating a more comprehensive scholarly examination. This study aims to analyze the contributions of the Fatimid Dynasty to the development of knowledge in Islamic civilization, focusing on its educational policies, the establishment of Al-Azhar and Dār al-Ḥikmah, the advancement of various branches of knowledge, and its influence on both the Islamic world and Europe. This research employs a historical approach using library research as its primary research design. Data were collected from books, peer-reviewed journal articles, and other relevant historical sources and were analyzed qualitatively through content analysis, with particular emphasis on the historical interpretation of the development of educational institutions and intellectual traditions during the Fatimid period. The findings reveal that the Fatimid Dynasty successfully established a conducive intellectual ecosystem through the founding of Al-Azhar University as a center of higher Islamic learning and Dār al-Ḥikmah as a center for research, library services, and the advancement of scientific knowledge. In addition to promoting the development of Islamic religious sciences, the Fatimid Dynasty also contributed significantly to the advancement of philosophy, medicine, astronomy, and mathematics. The academic tradition that flourished during this period strengthened the intellectual networks of the Islamic world and played an important role in the transmission of knowledge that subsequently contributed to the intellectual development of Europe. Therefore, the Fatimid Dynasty occupied a strategic position in fostering the Islamic scholarly tradition, leaving a lasting legacy for the development of world civilization.